Does Financing Decision Influence Corporate Performance in Malaysia? - Wan Daud, Wan Mohd Nazri; Norwani, Norlia Mat; Mansor, Anizawati Ahmad; Endut, Wan Anisah (International Journal of Economics and Financial Issues, 2016)
This paper examined the impact of financing decision on performance among Malaysian public listed firms in Bursa Malaysia. Previous studies did not examine the relationship between selection of capital structure and performance in the perspective of firms that implement industrial diversification strategy. This research comprised of 76 firms and covering balanced panel data series for the period of 1994-2007. The study observed that capitals structure has insignificant relationship with performance. However, it is recommended that firms should wary in using debt financing to finance business operation as it could lead to performance discount. Finding of the research contributed in explaining the capital structure decision made in the firms that implement industrial diversifications. Future research should investigate the option of firms that implement international diversification and its impact on corporate performance. Keywords: Financing Decision, Performance JEL Classifications: G30, G32